Integration of Shuttle Tourist Transport with Bus Rapid Transit (BRT) Metro Jabar Trans in Bandung Regency - I Made Suartika; Lintang Yunistriana (International Journal Labs, 2025)
Ciwidey in South Bandung is one of the leading tourist areas that requires good transportation accessibility. This study explores the integration of special shuttle services for tourists with the West Java Trans Metro Bus Rapid Transit (BRT) system in the area. The research approach includes literature review, policy analysis, transportation planning documents, interviews with relevant stakeholders, and comparative case studies with other cities/tourist areas. The results of the study revealed several main obstacles: weak institutional synergy between related agencies, inconsistencies in regulations governing tourism and public modes, and the issue of less integrated tariffs. For example, the Semarang study shows that most BRT stops do not have adequate intermodal integration facilities and Kebumen's analysis found that 89.55% of tourists are willing to choose the tour shuttle mode if cost and comfort are guaranteed Good practices from other cities, such as the integration strategy of public services in Yogyakarta can be used as a reference. This study concludes that strengthening institutional coordination, regulatory adjustments, and integrated tariff design are needed to facilitate modal integration.